Penyelesaian Pelanggaran Hak Asasi Manusia Yang Berat Masa Lalu Melalui Mekanisne Non-Yudisial (Studi Terhadap Keputusan Presiden Nomor 17 Tahun 2o22 Tentang Pembentukan Tim Penyelesaian Non Yudisial Pelanggaran Hak Asasi Manusia yang Berat Masa Lalu) - Yunita Syofyan; Didi Nazmi (LPPM Universitas Ekasakti Padang, 2023)
Based on Law No.26 of 2000 TentaofHuman Rights Court, apart from going through court, past serious human rights violations can be resolved through non-judicial mechanisms. Formation of a non-judicial resolution team for past serious human rights violations based on Presidential Decree Number 17 of 2022 whose task is to carry out non-judicial tasks to reveal cases of serious human rights violations and recommend concrete and dignified remedies for victims of serious human rights violations. Then. The question is, does the Non-Judicial Resolution Team for Past Serious Human Rights Violations have non-judicial authority in disclosing cases of past gross human rights violations?